Postoperative death investigation using a modified en bloc dissection of the kidney–ureter–bladder apparatus with postmortem contrast imaging: A case report on autopsy - Pradip Rana; Darshan Galoria; Srushti Shukla; William A. Cox; Prashant Verma; Shridhar Dave; Arijit Datta (SAGE Open Medical Case Reports)
Medicolegal autopsies should be performed for sudden, unexpected, and suspicious deaths. Such autopsies should be performed by a knowledgeable Forensic Pathologist who has experience in performing traditional autopsy techniques, as well as having an understanding of how to supplement these techniques with more scientifically advanced techniques such as magnetic resonance imaging and postmortem computed tomography. In this case, we utilized the traditional Ghon technique to remove the urogenital system, combined with postmortem computed tomography of the coronary arteries and contrast imaging of the ureters. By combining a traditional autopsy technique with more advanced imaging techniques, we were able to definitively establish the cause of death as coronary artery occlusion and, by doing so, remove any suspicion of medical negligence committed by the treating physicians during ureteroscopic bilateral stone removal.